The blink reflex in severely handicapped patients with dysphagia - Maeoka, Y; Eda, I (No to hattatsu, 1996)
We investigated the blink reflex in 27 severely handicapped patients. 15 males and 12 females, from 5 to 60 years old. They were divided into three groups; the tube-feeding group (9 patients), the oral-feeding group (9 patients), and the mixed-feeding group (9 patients). Seven normal subjects also were included in this study. There was a significant difference in the late ipsilateral component (R2) between the tube-feeding and oral-feeding groups. The average R 2 time were 43.0 msec. in the tube-feeding group and 36.7 msec. in the oral feeding group. The auditory brainstem response (ABR) showed no significant difference between the two groups. These results suggested that the swallowing function in the patients needed for tube feeding was affected by not only the cortical lesions but also the brainstem ones. Furthermore, it is speculated that the degree of brainstem dysfunction in the tube-feeding group was more severe than in the non-tube-feeding group. The blink reflex is one of the useful electrophysiological parameters for evaluating the brainstem function in severely handicapped patients with dysphagia.